Ratcheting behaviour of flash butt welds in heat-treated hypereutectoid steel rails under uniaxial and biaxial cyclic loadings. (15th June 2020) - Su, Hang; Li, Jian; Lai, Quan; Pun, Chung Lun; Mutton, Peter; Kan, Qianhua; Kang, Guozheng; Yan, Wenyi
Highlights: Uniaxial and biaxial stress-controlled cyclic tests were performed to investigate the ratcheting behaviour of flash butt welds in a heat-treated hypereutectoid steel rail. The distribution of ratcheting strain can be correlated to the longitudinal hardness profile within the heat-affected zone of the weld. At a same cyclic stress level, the softened zone exhibits a highest ratcheting strain, followed by the parent rail and the region near the bond line. At the initial stage of cyclic loading tests, the softened zone exhibits cyclic hardening while the region near the bond line exhibits cyclic softening. The spheroidised microstructure present in the softened zone significantly reduces its hardness and ratcheting resistance. Abstract: Experimental study consisting of both uniaxial and biaxial stress-controlled cyclic tests was performed to investigate the ratcheting behaviour of new flash butt welds in a heat-treated hypereutectoid steel rail used in Australian heavy haul railways. Digital image correlation technology was applied to capture the heterogeneous strain field and its evolution at every point on the surface of the weld specimen. The results show that the softened zone with a significant hardness drop is more sensitive to plastic deformation and results in a higher ratcheting strain than the region around the bond line. Moreover, the distribution of ratcheting strain can be correlated to the longitudinal hardness profile within the heat-affected zone of the weld. At the initial stage of cyclic tests, the softened zone tends to exhibit cyclic hardening while the region around the bond line is more likely to exhibit cyclic softening. Compared with the parent rail, the softened zone shows much worse ratcheting resistance, while the region around the bond line demonstrates slightly better ratcheting resistance. Metallographic analysis indicates that the microstructure and resulting ratcheting resistance of the weld vary with the longitudinal position. High ratcheting strain in the softened zone is mainly attributed to the existence of the spheroidised microstructure with a high amount of ferrite. The outcomes of this study can provide valuable information for further establishing the constitutive models to quantify the heterogeneous ratcheting of rail welds under practical wheel-rail contact situations by finite element simulations. Graphical abstract: Image, graphical abstract